Facile Synthesis of Graphene Oxide/Titanate Nanotube Composites and Their Application for Cobalt(II) Removal. (28th January 2022) - Xu, Min-Da; Jin, Zhen; Xie, Wen-Jie; Wang, De-Cai; Xu, Guang-Song; Wang, Ai-Jing; Zhang, Ran; Huang, Jian
Abstract : In this work, the novel graphene oxide/titanate nanotubes (GTNT) composites were synthesized through a facile and high-yield alkaline hydrothermal method. SEM, TEM, XRD, BET, and TGA/DTA were applied to study the morphology and structure of the GTNT composites. The results show that a huge number of titanate nanotubes are closely attached to the graphene sheet structure and overlap each other. This hierarchical morphology endows the GTNT composites with not only the high specific surface area of 236.9 m 2 /g but also abundant porous structure, both of which are benefit for Co(II) adsorption. The batch adsorption experiments demonstrate that the GTNT composites have a high adsorption capacity and rapid kinetics for Co(II) adsorption (10 min for equilibrium). The adsorption capacity of the GTNT composites reaches 211.1 mg/g. The adsorption kinetics of the GTNT composites fits well to the pseudo-second-order model, while the adsorption isotherm of which fits well to the Langmuir model. The adsorption performance of Co(II) ions on the GTNT composites has a great relationship with the pH value, in the pH range of 1–7, the Co(II) adsorption capacity of the GTNT composites greatly increases with the increase of the pH value. In addition, the effect of coexisting anions on fluoride removal is also investigated. Na +, K +, and Mg 2+ ions have shown a negligible effect on the Co(II) adsorption efficiency of the GTNT composites. However, the existences of Cu 2+, Cd 2+, and Pb 2+ ions would clearly have an effect on the Co(II) adsorption of the GTNT composites. The adsorption mechanism is also discussed. It is believed that the GTNT composites can be considered as a potential functional material for removing the radioactive metals containing wastewater.